Odpowiedzi

2010-02-27T16:11:42+01:00
9.
a)0,2x=-0,5-0,3 => x=-4
b)0,25x=-2-0,4 => x=-9,6
c)2,1=0,4x+0,3x => x=3
d)-1,5x-0,2x=9 => x=90/17
11.
a)(2x+3)/5=(2-x)/3-x
(2 x)/5+3/5 = (2-x)/3-x
x = 1/26
b)(x+1)/2-(x-1)/3=1/4
(1-x)/3+(x+1)/2 = 1/4
2 x+7 = 0
x = -7/2
c)(4x+7)/2-(5x-1)/6=x+5
1/6 (1-5 x)+1/2 (4 x+7) = x+5
1/6 (7 x+22) = x+5
(7 x)/6+11/3 = x+5
x = 8
d)(x+5)/4-(2x+1)/8=(2-x)2
1/8 (-2 x-1)+(x+5)/4 = 2 (2-x)
16 x = 23
x = 23/16
2010-02-27T18:19:10+01:00
9
a)
0,2x+0,3=-0,5
0,2x=-0,5-0,3
0,2x=-0,8 /:0,2
x=-4
b)
0,4+0,25x=-2
0,25x=-2-0,4
0,25x=-2,4 /:0,25
x=-9,6
c)
2,1-0,3x=0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1 /:(-0,7)
x=3
d)
-1,5x-3=0,2x+6
-1,5x-0,2x=6+3
-1,7x=9 /:(-1,7)
x=-9*10/17=-90/17=-5i5/17

11
a)równanie mnożymy przez wspólny mianownik 15
3(2x+3)=5(2-x)-15x
6x+9=10-5x-15x
6x+5x+15x=10-9
26x=1 /:26
x=1/26
b)równanie mnożymy przez wspólny mianownik 12
6(x+1)-4(x-1)=3
6x+6-4x+4=3
2x=3-6-4
2x=-7 /:2
x=-3,5
c)równanie mnożymy przez wspólny mianownik 12
6(4x-7)-2(5x-1)=12x+60
24x-42-10x+2=12x+60
14x-12x=60+40
2x=100
x=50
d)równanie mnożymy przez wspólny mianownik 8
2(x+5)-(2x+1)=4(2-x)
2x+10-2x-1=8-4x
4x=8-9
4x=-1 /:4
x=-1/4


:)

Najlepsza Odpowiedź!
2010-02-27T19:32:01+01:00
9.a)0,2x=-0,5-0,3 => x=-4
b)0,25x=-2-0,4 => x=-9,6
c)2,1=0,4x+0,3x => x=3
d)-1,5x-0,2x=9 => x=90/17

11.a)(2x+3)÷5=(2-x)÷3-x
(2 x)÷5+3/5 = (2-x)÷3-x
x = ¹/₂₆
b)(x+1)÷2-(x-1)÷3=¼
(1-x)÷3+(x+1)/2 =¼
2 x+7 = 0
x = -⁷/₂=-3½
c)(4x+7)÷2-(5x-1)÷6=x+5
⅙ (1-5 x)+½ (4 x+7) = x+5
⅙ (7 x+22) = x+5
(7 x)/6+11÷3 = x+5
x = 8
d)(x+5)÷4-(2x+1)÷8=(2-x)2
⅛ (-2 x-1)+(x+5)÷4 = 2 (2-x)
16 x = 23
x =²³/₁₆
1 5 1